2009
DOI: 10.1038/msb.2009.82
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in growth strategies reflect tradeoffs in cellular economics

Abstract: The growth rate-dependent regulation of cell size, ribosomal content, and metabolic efficiency follows a common pattern in unicellular organisms: with increasing growth rates, cell size and ribosomal content increase and a shift to energetically inefficient metabolism takes place. The latter two phenomena are also observed in fast growing tumour cells and cell lines. These patterns suggest a fundamental principle of design. In biology such designs can often be understood as the result of the optimization of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
840
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 614 publications
(872 citation statements)
references
References 57 publications
31
840
0
1
Order By: Relevance
“…the lag phase or even the strict sequential nature of nutrient uptake. This is confirmed by recent experimental findings that demonstrate this plasticity using artificial wet-lab evolution (Molenaar et al, 2009). For as long as the plasticity of dual nutrient uptake is established, then the details of the implementation are mostly irrelevant.…”
Section: Discussionsupporting
confidence: 79%
“…the lag phase or even the strict sequential nature of nutrient uptake. This is confirmed by recent experimental findings that demonstrate this plasticity using artificial wet-lab evolution (Molenaar et al, 2009). For as long as the plasticity of dual nutrient uptake is established, then the details of the implementation are mostly irrelevant.…”
Section: Discussionsupporting
confidence: 79%
“…Both mechanisms together produce global changes that reorganize that metabolic network for optimal growth. The use of energy inefficient and wasteful metabolite overflow appears to be an essential trade-off to achieve fast growth under conditions where carbon source is abundant, as suggested by other studies 31,33 . It will be interesting to see how the optimized network of the fast growing mutants described here fares under nutrient-limiting conditions where biosynthetic and efficiency requirements and priorities are different.…”
Section: Discussionmentioning
confidence: 65%
“…Prior studies have suggested that less efficient overflow metabolism may be advantageous when carbon source is non-limiting and protect against methylglyoxal toxicity 30 . Overflow has also been proposed to represent a trade-off between energy and biomass yield and the biosynthetic costs of respiration that occur during fast growth 31 . In addition, competition for membrane space between substrate uptake and respiration has also been proposed to be a constraint leading to carbon wasting 32 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the importance of these constraints in predicting cellular growth and reaction rates, we compared nonlinear simulations of a simplified whole-cell metabolic model (based on previous work [MvBdRT09]) to FBA and to FBA with molecular crowding. FBA growth rate predictions are realistic only at low growth rates, while FBA with molecular crowding provides qualitatively acceptable predictions at all growth rates.…”
Section: Prioritizing Cancer Driver Genes With Contrastrankmentioning
confidence: 99%